AWS Developer - Garner, Nick (Pearson, 2024)
AWS Certified Developer - Associate (DVA-C02) is your complete study resource covering all the objectives in the DVA-C02 exam. Throughout this course, you will explore a multitude of AWS services, dive into hands-on exercises, and learn best practices for developing, deploying, and debugging cloud-based applications on AWS. You will also navigate the vast landscape of AWS SDKs and APIs and understand how to leverage them effectively. With expansive coverage of all topics contained in the Exam Guide this course not only covers all the objectives in the exam; it also provides hands-on and in-depth demos throughout so you can see AWS in action and learn real-world skills. This course takes a per-domain approach with an understanding that the prerequisite service-level basics are already understood. Hands-on Development in AWS covers the core development topics you need to really create applications while providing a deeper exploration of cloud services so you can fully understand the work. Topics covered include AWS foundations services like identity and access management and Virtual Private Cloud, databases and storage services, execution services of AWS, and finally cover the development of apps in AWS including AWS API, AWS SDKs, CloudFormation, and AWS Developer Tools.
Online resource; title from title details screen (O'Reilly, viewed June 24, 2024)
Keywords: Amazon Web Services (Firm) -- Study guides -- Examinations; Web services -- Study guides -- Examinations; Cloud computing -- Study guides -- Examinations; Application software -- Study guides -- Development; Electronic data processing personnel -- Certification; Streaming video; Services Web; Examens; Guides de l'étudiant; Logiciels d'application; Développement; Guides de l'étudiant; Vidéo en continu; streaming video; Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet